If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -7(5 + y) = 0 4y + (5 * -7 + y * -7) = 0 4y + (-35 + -7y) = 0 Reorder the terms: -35 + 4y + -7y = 0 Combine like terms: 4y + -7y = -3y -35 + -3y = 0 Solving -35 + -3y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -3y = 0 + 35 Combine like terms: -35 + 35 = 0 0 + -3y = 0 + 35 -3y = 0 + 35 Combine like terms: 0 + 35 = 35 -3y = 35 Divide each side by '-3'. y = -11.66666667 Simplifying y = -11.66666667
| N/2-6=5 | | 1.32/.5 | | -2y+10=-6y-22 | | 9-5x=6x+4 | | n-(-2)=10 | | x/6=x/7=6/7 | | b^2+10b+42= | | x+11x=-84 | | 4(3x-2)=5x-(3-6x) | | (2-w)(4w+7)=0 | | 4(3-2x)-7=2x | | 2x-y=35 | | 14s=16(s+12) | | x^6-9x^3+14= | | (5+u)(2u+7)=0 | | 1-cosx/4x^2 | | 2+7x=8+6x | | 78.34m= | | 2s+2(2-40)=440 | | 110x=12.5 | | 180/15(15-2) | | m-3=-3.19 | | 5x-3=x+10 | | 13x+1=11x+5 | | 6(d-8)=-12 | | 41-a=3(a-5) | | 6(d-8)=-11 | | v=3/8x12 | | 7(p+2)=9-p | | -2x=6/13 | | 2/3x-3/4=5/8 | | J/3-J-3/6=7/6 |